2009
DOI: 10.1002/app.30709
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface esterification with octenyl succinic anhydride on hydrophilicity of corn starch films

Abstract: Surface of corn starch films was modified through esterification using octenyl succinic anhydride as reactant. Physical properties of the films, moisture absorption, and water contact angle were measured to characterize the effect of the surface esterification modification. The influences of the concentration of alkaline aqueous solution for activating starch, reaction temperature, and time were investigated. It was found that the pretreatments with 1.0% or 2.0% NaOH aqueous solution and reacting at 35 C for 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The standard Tappi T559 pm-96 method was employed to evaluate grease resistance. Papers were tested using a selection of solutions with different Kit numbers (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), which contained three reagents (castor oil, n-heptane and toluene) in specific proportions. Kit number 1 with the highest surface energy, and Kit number 12 with the lowest surface energy, were the least and most aggressive oils, respectively.…”
Section: Oil and Grease Resistance Kit Test Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The standard Tappi T559 pm-96 method was employed to evaluate grease resistance. Papers were tested using a selection of solutions with different Kit numbers (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), which contained three reagents (castor oil, n-heptane and toluene) in specific proportions. Kit number 1 with the highest surface energy, and Kit number 12 with the lowest surface energy, were the least and most aggressive oils, respectively.…”
Section: Oil and Grease Resistance Kit Test Proceduresmentioning
confidence: 99%
“…Therefore, during surface sizing of high grade paper and oxidized starch has gradually been replaced with cationic starch and other starches with a high retention rate . To improve the water resistance of biopolymer films, several strategies have been investigated, including (1) blending with lipids such as stearic acid, palmitic acid, oleic acid, and beeswax; (2) blending with polymers such as carboxymethyl and nanocrystalline cellulose; and (3) hydrophobization of biopolymers such as esterification with octenylsuccinic anhydride (OSA) . Moisture‐proofing of stretchable sweet potato starch film can be enhanced by incorporating octenylsuccinated starch .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…95 Singh et al 94 synthesized acetylated corn and potato starches in NaOH solution, which showed higher solubility, swelling power and light transmittance than the native starch. Zhou et al 20 investigated the inuence of surface esterication on moisture absorption behavior and optimal conditions for esterication. Winkler et al 95 compared lauric acid vinyl esterication (Scheme 2a) and lauroyl chloride esterication (Scheme 2b).…”
Section: Inorganic Starch Estersmentioning
confidence: 99%
“…Another aspect requiring attention is its tendency to crystallize during storage which makes it brittle. Consequently, various chemical modifications of TPS have been created to address these problems [5][6][7].…”
Section: Introductionmentioning
confidence: 99%